2002
DOI: 10.1103/physrevb.66.064432
|View full text |Cite
|
Sign up to set email alerts
|

Dirty spin ice: The effect of dilution on spin freezing inDy2Ti2O

Abstract: We have studied spin freezing in the diluted spin ice compound Although geometrical magnetic frustration has been most extensively studied in materials with antiferromagnetic nearest-neighbor interactions, the effects of strong frustration have also been found in the so-called "spin ice" materials (such as Dy 2 Ti 2 O 7 , Ho 2 Ti 2 O 7 , and Ho 2 Sn 2 O 7 ) [ 3,4,5,6,7,8,9,10,11,12] in which ferromagnetic and dipolar interactions can be frustrated [13,14,15,16]. The spins in these compounds are governed by the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 37 publications
4
33
0
Order By: Relevance
“…The data presented here enable one to study the relaxation process in spin ice at temperatures lower than those for which ac-susceptibility data are available 20,34 and to compare the influence of magnetic dilution on spin relaxation in the milikelvin temperature range with the detailed investigations reported for T > T ice 21 . The thermal response of Dy 2 Ti 2 O 7 on decreasing magnetic field suggests that above ∼ 0.4 K the magnetic and lattice/thermometer subsystems are in thermal equilibrium during the demagnetization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data presented here enable one to study the relaxation process in spin ice at temperatures lower than those for which ac-susceptibility data are available 20,34 and to compare the influence of magnetic dilution on spin relaxation in the milikelvin temperature range with the detailed investigations reported for T > T ice 21 . The thermal response of Dy 2 Ti 2 O 7 on decreasing magnetic field suggests that above ∼ 0.4 K the magnetic and lattice/thermometer subsystems are in thermal equilibrium during the demagnetization.…”
Section: Discussionmentioning
confidence: 99%
“…Acsusceptibility studies of powdered Dy 2 Ti 2 O 7 up to 20 K suggest rather a wide distribution of relaxation times 18 , but other studies 19 suggest that spin ice responds to external magnetic field in a very limited range of relaxation times, an effect that has been ascribed to the high degree of chemical and structural order. In addition, acsusceptibility data for Dy 2 Ti 2 O 7 indicate strongly frequency dependent spin freezing at about 16 K. This was initially discussed in terms of collective dynamics, 19,20 , but subsequently, on the basis of systematic studies of Dy 2−x Y x Ti 2 O 7 in wide range of dilutions x 21 as well as neutron scattering 22 , ascribed to a single spin flip process.…”
Section: Introductionmentioning
confidence: 99%
“…Because there has been no indication of a structural phase transition at low temperatures in the small rare earth titanate pyrochlores (magnetic ordering at low temperatures has been observed of course) in any of the many characterization experiments performed previously [see, e.g. 2,18,19], the Fd-3m symmetry must by inference be maintained to very low temperatures. However, to be sure about this, here we confirm this inference through performing a high-sensitivity synchrotron X-ray diffraction measurement on Ho 2 Ti 2 O 7 at 10 K.…”
Section: Introductionmentioning
confidence: 99%
“…Dilution studies on spin ice materials, [15][16][17] where magnetic rare earth moments are replaced with a nonmagnetic species, reveal that decreasing the spin interactions does not destroy the icelike state, but does suppress the magnitude of the freezing signature. It was recently shown that "stuffed spin ice"-the opposite case where additional magnetic atoms are stuffed into the nonmagnetic Ti sites creating, for example, the series Ho 2 ͑Ti 2−x Ho x ͒O 7−x/2 , 0 ഛ x ഛ 0.67-retains the same zero-point entropy as undoped spin ice and may possess accelerated spin dynamics.…”
Section: Introductionmentioning
confidence: 99%